A molecular fluorescent dye for specific staining and imaging of RNA in live cells: a novel ligand integration from classical thiazole orange and styryl compounds. Issue 83 (2nd September 2015) - Lu, Yu-Jing; Deng, Qiang; Hu, Dong-Ping; Wang, Zheng-Ya; Huang, Bao-Hua; Du, Zhi-Yun; Fang, Yan-Xiong; Wong, Wing-Leung; Zhang, Kun; Chow, Cheuk-Fai
Abstract : A new RNA-selective fluorescent dye shows excellent nucleolus RNA staining and imaging performance in live cells. Abstract : A new RNA-selective fluorescent dye integrated with a thiazole orange and a p -(methylthio)styryl moiety shows better nucleolus RNA staining and imaging performance in live cells than the commercial stains. It also exhibits excellent photostability, cell tolerance, and counterstain compatibility with 4′, 6-diamidino-2-phenylindole for specific RNA–DNA colocalization in bioassays.